All-optical gain-clamped erbium-doped fiber-ring lasing amplifier with laser filtering technique - Subramaniam, T.; Mahdi, Mohd Adzir; Poopalan, Prabakaran; Harun, Sulaiman Wadi; Ahmad, Harith (Institute of Electrical and Electronics Engineers (IEEE), 2001)
A unique laser filtering technique of a gain-clamped erbium-doped fiber amplifier based on ring-laser cavity is demonstrated. The filtering mechanism is achieved using a single fiber Bragg-grating, which also functions as a laser feedback reflector at the output end of the amplifier. This new design has low noise and most important, shows up to 98% reduction in output laser intensity as compared with a previous design studied earlier. An optimum result with gain and noise around 25 and 3.5 dB, respectively, obtained for a dynamic range of input signal power up to -8 dBm.